INTERRELATIONS OF THE STRUCTURAL AND FUNCTIONAL COMPONENTS OF DECEIT WITH PERSONALITY TRAITS IN WOMEN - CRIMINALS AND WOMEN WITH CONDITIONAL-NORMATIVE BEHAVIOR - Toporkova, Inna (PSYCHOLOGICAL JOURNAL, 2018)
The purpose of the article is to empirically reveal the interrelations between the structural and functional components of deceit with personality traits in women - criminals and women with conditional-normative behavior. The empirical base of the study was made by 124 women convicted of crimes that are somehow connected with deception (the criminal executive institution of the minimum level of security with the general conditions for keeping women, Kharkov), as well as women with conditional normative behavior (124 people). All subjects aged 35-45 years. The research methods were the structural and functional questionnaire of mendacity IA. Church, Freiburg personal questionnaire, created for applied research, diagnosis of conditions and personality characteristics that are important for the process of social adaptation and regulation. For the mathematical-statistical processing of the results, the Spearman rank correlation coefficient was applied. The obtained empirical results testify to the differences in the structure of the interrelations between the structural and functional components of deceit and personality traits in groups of female criminals and women with conditional normative behavior. These groups differ both in the number of significant correlations and in their content. In the group of women with conditionally normative behavior, ten significant correlations were found, seven of which are positive, and three are negative. In the group of female criminals, seven significant relationships were identified, all of which are positive. In addition, the revealed relationships in the study groups are significantly different. For women with conditionally normative behavior, almost all components of deceit are involved - dynamic, regulatory (personal characteristics depend on individual characteristics, that is, on the character and nervous system) - motivational, cognitive, productive (personal characteristics depend on social factors of development and from the social environment, conditions of activity). And in the group of female criminals, there are interrelations between personality traits and the structural and functional components of deceit of dynamic, regulatory, cognitive and productive nature (dynamic aerogicality, regulatory externalities, cognitive meaning, objective effectiveness). In this way, the falsity in the group of female criminals is manifested in the denial of independence, activity, in fear of exposure; in the denial of their dependence on other people or external circumstances, if their own obligations are not fulfilled, while denying their own importance; when demonstrating the independence of decision-making, expressing one’s own opinion; when demonstrating the focus on a socially significant result, with a false desire for self-realization, a desire to achieve positive relations with others. Also, unlike women with conditional-normative behavior, female criminals have more pronounced agarmonic variables (“aerogism”, “externality”), closely related to such personal traits as neuroticism, irritability, reactive aggressiveness, depressiveness.